Koordinasi Pengakuan Dan Pengukuhan Masyarakat Hukum Adat di Kabupaten Ogan Komering Ilir - Yahya, Amril; Idi, Abdullah; Sutinah, Sutinah (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
Ogan Komering Ilir Regency, there are several residents who claim that their area contains customary land. This claim has the potential to cause conflict if it is involved with companies that have operations in Ogan Komering Ilir Regency, such as plantation, forestry and mining companies. To prevent conflicts between residents and these companies, identification, verification and validation need to be carried out to determine whether these residents are indeed included in the category of Indigenous Peoples. By having clarity regarding their status, the government can take policies that are fair to all parties involved. The aim of this research is to coordinate the recognition and confirmation of Indigenous Law Communities in OKI Regency. The method used in this research is a qualitative descriptive method, involving informants from the Land Service and community leaders at OKI. The research results show that: 1) The process of coordinating the recognition and inauguration of Customary Law Communities in OKI Regency has been carried out optimally by responsible employees, in accordance with OKI Regent Decree Number 6 of 2021 concerning the Establishment of a Team for Coordination and Synchronization of Recognition and Inauguration of Customary Law Communities in OKI Regency area. 2) Coordination of recognition and inauguration of Indigenous Law Communities in OKI Regency has gone well and involves collaboration with the local government and other stakeholders. Thus, the steps that have been taken to identify and recognize the status of Indigenous Peoples in OKI Regency have been carried out optimally and have involved good cooperation between the government and related parties.